Rethinking Socialist Space in the Twentieth Century
XIII, 338 p. 26 illus., 20 illus. in color.
Keywords: “This skillfully crafted collection shows both the roominess of socialist space as a category of analysis and also its rich and productive potential. A series of imaginative essays explore socialist spatiality across multiple continents as a dynamic and physically and experientially diverse dimension of twentieth-century history.” —Kristin Roth-Ey, University College London, UK “Utilising the tools of spatial history, this volume impressively brings together geographically diverse and methodologically innovative case studies into a collection that provides rich insights into questions of (im)mobility, locality and border crossing, and hierarchies of internationalism, in the socialist world of the Cold War - from East Asia to the Soviet Union to West Africa.” — James Mark, University of Exeter, UK This edited collection explores the problem of space under socialist regimes in the twentieth century. Bringing together contributions from international scholars with expertise in the architectural, urban, social, and cultural history of twentieth-century socialism, the book includes examples from China, Africa, Mongolia, Eastern Europe, and the USSR. The volume reflects on how developments in the field over the past two decades have altered our understanding of how such spaces were constructed (both literally and discursively), how they could become sites of contested meanings, and how they were perceived outside the socialist world. Moreover, the volume is concerned with how scholarly approaches associated with post-colonialism, global history, gender history, and the ‘temporal’ and ‘sensory’ turns have reconfigured our knowledge of, and approach to, the history of socialist space. Marcus Colla is Associate Professor of Modern European Political History at the University of Bergen, Norway. His first book, Prussia in the Historical Culture of the German Democratic Republic: Communists and Kings, was published in 2022. Paul Betts is Professor of Modern European History at St Antony’s College at the University of Oxford, UK. His most recent works include Ruin and Renewal: Civilising Europe after World War II (2022), and a co-written volume Socialism Goes Global: The Soviet Union and Eastern Europe in the Age of Decolonisation (2023). .